On a QoS intrusion tolerant routing protocol in ad-hoc networks - Boudriga, Noureddine (2006)
We propose in this paper a protocol, called QITAR, which will secure the ad-hoc routing process while guaranteeing end-to-end QoS requirements in terms of delay or bandwidth constraints. Our approach provides an intrusion tolerant environment and uses and enhances the concept of Trusted Timely Computing Base in order to deduce consistent delay information and verify the bandwidth value pretended by untrusted nodes. QITAR also proposes a rescue procedure that saves the resources and accelerates the route maintenance in case of node mobility